Perbandingan Metode SAW, WP dan TOPSIS dalam Sistem Penunjang Keputusan Pemilihan Smartphone Android Bekas - Muhamad Burhanudin; Satria Putra Laksmana; Diva Ikbar Rauf; Damar Wicaksono; Perani Rosyani (CV. Multi Kreasi Media, 2023)
Smartphones are one of the imperative needs for today's society. The advancement of communication innovation has had a major affect on the advance of smartphone innovation, which has gotten to be a challenge in making the choice to select an Android smartphone. Money related reasons and the require for tall determinations in buying an Android smartphone are factors that are taken into thought in making a choice to select an Android smartphone, so it isn't unprecedented for individuals to incline toward to purchase a smartphone in utilized condition which of course has dangers and tends to have no item ensures such as buying in unused conditions. The nearness of a Choice Support System (DSS) may be a arrangement to this issue, by utilizing an DDS one can more easily and dispassionately select a utilized smartphone so as to induce the ideal choice. A Choice Back Framework in other dialects is additionally known as a Choice Back Framework (DDS) is an intuitively data framework where this framework gives modeling, data and. The weighting of the criteria is done by implies of a survey to arbitrary individuals to discover out what individuals think around the foremost critical criteria in choosing a utilized smartphone. After calculating the 4 choices with 3 thought processes, the comes about can be concluded that Elective 2 (SS World A04) continually gets the most noteworthy score with a value of 15.00 within the SAW strategy calculation, 0.37 within the WP strategy calculation and 0.83 utilizing the TOPSIS strategy. so Elective 2 can be utilized as a proposal for choice making in choosing a utilized Android smartphone